An exploration of grade 4 teachers' understanding and practice of formative assessment in Mathematics - Tripp, Jacob Mark Anthony (University of the Witwatersrand, Johannesburg, 2024)
This qualitative case study examined grade 4 teachers' understanding and implementation of formative assessment in mathematics at a South African private school. The study employed semi-structured interviews with three teachers and observations of nine lessons to develop insights into how educators conceptualize and apply formative assessment strategies. Thematic analysis revealed that while teachers demonstrated strong theoretical knowledge of formative assessment during interviews, classroom practices showed inconsistencies and missed opportunities for effective integration. Key findings indicated gaps in translating conceptual understanding into consistent, high-quality formative routines. Instruction often conflated formative and summative purposes, with an over-reliance on teacher judgments rather than eliciting student thinking. Despite recognizing the value of descriptive feedback, crucial opportunities were missed to provide specific guidance to advance learners' mathematical comprehension. Challenges in implementing formative assessment stemmed from time constraints, difficulties managing differentiation, and determining appropriate pedagogical responses based on assessment insights. The overarching issue was the struggle to operationalize theoretical understanding into routines that unveil and responsively scaffold students' emerging mathematical proficiencies. The study highlights the need for ongoing professional development, collaborative planning, and coaching to bridge the theory-practice divide. Leveraging technology and resources could alleviate logistical constraints. Recommendations aim to foster a culture of continuous learning and responsiveness to students' evolving needs. Effective formative assessment has the potential to enhance engagement, conceptual understanding, and achievement in mathematics.
A research report submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; formative assessment; Methametics; Primary school; SDG-4: Quality education